DIGITALIZING ISLAMIC CONTRACTS: CULTURAL AND REGULATORY REFLECTIONS ON SMART CONTRACTS IN INDONESIA’S FINTECH SHARIA ECOSYSTEM - Warda Lutfiah (Smart Education, 2026)
The development of blockchain technology has brought significant innovation to the Islamic finance industry, particularly in the sharia peer-to-peer (P2P) lending fintech sector. One of the main components of this technology, namely smart contracts, offers opportunities to strengthen sharia principles such as fairness, transparency, and efficiency in financial transactions. This study aims to analyze the implementation of smart contracts in the Islamic P2P fintech ecosystem in Indonesia through literature review and analysis of applicable regulations. The results show that although smart contracts have the potential to support maqÄá¹£id al-sharÄ«â€˜ah, their successful implementation is highly dependent on regulatory readiness, understanding of fiqh muamalah, and the digital literacy of the Muslim community. Sociologically and culturally, smart contracts also reflect a shift in contract practices from traditional to digital forms, challenging the authority of conventional scholars and opening up space for technological ijtihad in Indonesian Muslim society. This study contributes to the understanding of how Islamic values can be transformed contextually in the face of digital change, as well as offering normative reflections on the integration of technology in contemporary sharia economic practices